ASPECTS ABOUT THE RECOVERY OF THE AUTIST CHILD THROUGH KINETIC AND LUDOTHERAPY RESOURCES - Oltean Anca-Maria; Jacek Sobon (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
"Autism" is a linguistic label; a name for a mental disorder that appears very early in human development and affects the most basic skills such as: communicating and human interaction. Autism is the most common pervasive developmental disorder (ASD). It presents itself as a global disease that affects skills and deficits that range from one person to another. Autistic people present an individualized combination and distinctive needs and qualities. Autism is the most severe development disorder that causes disorders in three main areas: communication, behavior and social interaction. Ludotherapy is a form of available activity that solves one or more therapeutic tasks through the exercise of complex movements, stimulating game features playing sports or handling simple objects. Playing causes children with disabilities the training and development of spontaneous motor acts that they can't do voluntarily or on demand.